Assessment of the quality of life of patients with type 2 diabetes mellitus and associated variables - Mariana Caroliny Ferreira; André Oliveira Baldoni; Caroline Pereira Domingueti (Brazilian Journal of Health and Pharmacy, 2025)
Introduction: The lifelong treatment, comorbidities and complications of type 2 diabetes mellitus (T2DM) may result in compromised patients’ quality of life (QOL). This study aimed to evaluate the QOL of patients with T2DM and analyze the association between clinical, sociodemographic and laboratory variables with the QOL. Methods: A cross-sectional study was carried out in 265 patients with T2DM treated at the Basic Health Units. QOL, knowledge and attitude were evaluated by validated questionnaires. Clinical, sociodemographic and laboratory data were coll ected. Results: Among patients interviewed, 53.6% had good, 31.7% very good, 10.9% regular and 3.8% excellent QOL. The levels of glycated hemoglobin (HbA1c), isolated albuminuria and urinary albumin/creatinine ratio were higher in the group of patients with regular QOL than in the group with good, very good or excellent QOL. The group with regular QOL had a higher proportion of individuals with HbA1c levels ≥ 7.0%, high-density lipoprotein cholesterol ≤ 50 mg/dL and isolated albuminuria ≥ 174 mg/L compared to the group with good, very good or excellent QOL. Knowledge and attitude towards T2DM had no impact on QOL, whereas female sex was independently associated with regular QOL. Conclusion: Poor glycemic control, increased albuminuria, reduced high-density lipoprotein cholesterol levels were more frequent in T2DM patients with regular QOL and female sex were independently associated with regular QOL.